2014
DOI: 10.4236/jep.2014.59078
|View full text |Cite
|
Sign up to set email alerts
|

Government and Community Involvement in Environmental Protection and Flood Risk Management: Lessons from Keko Machungwa, Dar es Salaam, Tanzania

Abstract: Since the 1960s, most cities in developing countries have faced a high rate of urbanization, which in turn has caused more harm to low-income earners, in urban areas. A majority of low-income earners most often face difficulties in accessing land in planned areas, as a result they are forced to build houses in unplanned settlements that are vulnerable to natural hazards. The situation is worse to the extent that people encroach the most vulnerable areas (hazard lands). As concentration of people increases, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…The high cost charged could be one of the reasons why very few respondents use gulper empting services. In an interview with one respondent it was revealed that flooding and poor solid waste management also contributes to the poor sanitary conditions in Keko Machungwa, this finding is similar to the findings by Sakijege et al (2014) and Kasala (2014). Evans (2005) and WHO (2014) have argued that efforts to improve sanitation need to consider initiatives beyond construction of improved toilets.…”
Section: Other Efforts Made On Improved Sanitation Latrines In Partisupporting
confidence: 73%
See 4 more Smart Citations
“…The high cost charged could be one of the reasons why very few respondents use gulper empting services. In an interview with one respondent it was revealed that flooding and poor solid waste management also contributes to the poor sanitary conditions in Keko Machungwa, this finding is similar to the findings by Sakijege et al (2014) and Kasala (2014). Evans (2005) and WHO (2014) have argued that efforts to improve sanitation need to consider initiatives beyond construction of improved toilets.…”
Section: Other Efforts Made On Improved Sanitation Latrines In Partisupporting
confidence: 73%
“…12 of 2009. The Act provides that… every person in Tanzania has to have access to effective, efficient, and sustainable sanitation services… The poor toilet conditions found in the two cases, reaffirm the views aired by (Hutton, Haller, & Bartram, 2007), and Sakijege et al (2014) and other scholars that, sanitation provision in Dar es Salaam and in other cities of developing countries is deficient.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations